2021
DOI: 10.1177/1477153520982371
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acute alerting effects of a daylight-supplementing in-vehicle lighting system – Results from two randomised controlled field studies during dawn and dusk

Abstract: The present studies examined the feasibility and acute alerting effects of additional in-vehicle lighting within a passenger car. These factors were examined during morning driving (Study 1) and evening driving (Study 2). In a balanced within-subjects design, 37 participants drove a test car two times in the morning or in the evening. The test vehicle was equipped with either a daylight-supplementing interior lighting system or a placebo system, which participants were told would refresh the air. Both studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Sensations generated from the living space are similarly applicable in the vehicle context. Researchers have explicitly explored controlling attributes of in-vehicle ambient light such as animations [36], brightness [14], color [12], and distribution [13]. orange-enriched white lighting, often labeled as warm white light, created a luxurious atmosphere in the vehicle regarding the influence of color and brightness of the illuminants within the vehicle environment [13].…”
Section: Related Work a The Potential Of Lighting Behaviors In Vehicl...mentioning
confidence: 99%
See 4 more Smart Citations
“…Sensations generated from the living space are similarly applicable in the vehicle context. Researchers have explicitly explored controlling attributes of in-vehicle ambient light such as animations [36], brightness [14], color [12], and distribution [13]. orange-enriched white lighting, often labeled as warm white light, created a luxurious atmosphere in the vehicle regarding the influence of color and brightness of the illuminants within the vehicle environment [13].…”
Section: Related Work a The Potential Of Lighting Behaviors In Vehicl...mentioning
confidence: 99%
“…In contrast, blue-enriched white lighting, frequently labeled as cool white light, more effectively influences drivers' awakening state [12]. Another study indicated that variation of brightness of blue-enriched white light controlled humans' physiological status, including alertness [14].…”
Section: Related Work a The Potential Of Lighting Behaviors In Vehicl...mentioning
confidence: 99%
See 3 more Smart Citations